2017
DOI: 10.5812/semj.14565
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Small Access and Classic McBurney’s Incisions for Open Appendectomy: A Randomized Controlled Trial

Abstract: Background: Many surgeons have been encouraged to use a variety of incisions for abdominal visceral surgery that are hidden from exposure. The current researchers conducted this study to find the safety and feasibility of open appendectomy using Small Access (SA) incision and compare this method with the classic McBurney's appendectomy (CA). Methods: Sixty-nine patients with the diagnosis of acute appendicitis at Besat hospital, Hamadan University of Medical Sciences, Iran, during year 2016, were enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The amount of pain medication administered during the hospital stay in the small incisopn appendectomy group was significantly lower than the conventional appendectomy group. 11 A new small access incision was introduced by Malik et al 12 The incision is 1.5 to 2 cm in length, located in the middle third of the lateral third of the spinoumbilical line, lateral to McBurney's point. It has been shown that appendectomy using this method is feasible in children with advantages of less postoperative pain, shorter hospital stay, and better cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of pain medication administered during the hospital stay in the small incisopn appendectomy group was significantly lower than the conventional appendectomy group. 11 A new small access incision was introduced by Malik et al 12 The incision is 1.5 to 2 cm in length, located in the middle third of the lateral third of the spinoumbilical line, lateral to McBurney's point. It has been shown that appendectomy using this method is feasible in children with advantages of less postoperative pain, shorter hospital stay, and better cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were seen in Bhasin et al study where analgesics used in mini appendectomy were less, that is, 2.13 doses against 4.2 doses in conventional appendectomy group. Similarly in Javadi et al [5] study, the amount of analgesics administered during the hospital stay in small access group (110±29.2 mg) was lower than the conventional appendectomy group (134±29.7 mg).…”
Section: Singh Et Almentioning
confidence: 52%